2019
DOI: 10.1016/j.neuropharm.2019.02.010
|View full text |Cite
|
Sign up to set email alerts
|

MP1104, a mixed kappa-delta opioid receptor agonist has anti-cocaine properties with reduced side-effects in rats

Abstract: Kappa opioid receptor (KOPr) agonists have preclinical anti-cocaine and antinociceptive effects. However, adverse effects including dysphoria, aversion, sedation, anxiety and depression limit their clinical development. MP1104, an analogue of 3-iodobenzoyl naltrexamine, is a potent dual agonist at KOPr and delta opioid receptor (DOPr), with full agonist efficacy at both these receptors. In this study, we evaluate the ability of MP1104 to modulate cocaine-induced behaviors and side-effects preclinically. In mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 106 publications
5
23
0
Order By: Relevance
“…An ex vivo analysis also using voltammetry in disaggregated tissues, showed that a systemic injection of KOR agonist U-69593 increased dopamine uptake in the NAc (Thompson et al, 2000). A similar recent article shows that nor-BNI blocks the increase of dopamine uptake in the ventral and dorsal striatum, induced by an acute systemic injection of MP1104, a mixed Kappa/Delta opioid receptor agonist (Atigari et al, 2019). Nevertheless, the effect of KOR activation on dopamine uptake has yet not been not fully elucidated.…”
Section: Striatal Regionsmentioning
confidence: 94%
“…An ex vivo analysis also using voltammetry in disaggregated tissues, showed that a systemic injection of KOR agonist U-69593 increased dopamine uptake in the NAc (Thompson et al, 2000). A similar recent article shows that nor-BNI blocks the increase of dopamine uptake in the ventral and dorsal striatum, induced by an acute systemic injection of MP1104, a mixed Kappa/Delta opioid receptor agonist (Atigari et al, 2019). Nevertheless, the effect of KOR activation on dopamine uptake has yet not been not fully elucidated.…”
Section: Striatal Regionsmentioning
confidence: 94%
“…MP1104 produced potent antinociceptive effects in the radiant heat tail-withdrawal assay in male CD1 mice (Varadi et al, 2015) and reduced inflammatory pain in the intradermal formalin test in both male and female ICR mice (Ulker et al, 2020) (Table 2). Moreover, MP1104 has anti-cocaine effects in male Sprague-Dawley rats and showed no anxiogenic, pro-depressive, or aversive side-effects (Atigari et al, 2019).…”
Section: D) Partial Kopr Agonism With Partial Mopr Agonism/antagonismmentioning
confidence: 99%
“…In vitro analysis revealed MP1104 had 3-and 13-fold higher selectivity for the κ receptor than the μ receptor and δ receptor respectively, with full agonism at all three receptors (Váradi et al, 2015). While in vivo it has been shown to induce potent, long acting anti-nociception in the tail-flick assay in both rats and mice and attenuates cocaine self-administration in rats (Atigari et al, 2019, Váradi et al, 2015. Furthermore, it does not induce anxiogenic or aversive effects as measured by elevated plus maze, forced swim test, and conditioned place aversion in rats (Atigari et al, 2019).…”
Section: Alternative Paths To Non-addictive Analgesicsmentioning
confidence: 99%
“…While in vivo it has been shown to induce potent, long acting anti-nociception in the tail-flick assay in both rats and mice and attenuates cocaine self-administration in rats (Atigari et al, 2019, Váradi et al, 2015. Furthermore, it does not induce anxiogenic or aversive effects as measured by elevated plus maze, forced swim test, and conditioned place aversion in rats (Atigari et al, 2019). Ultimately, these μ receptor/ κ receptor mixed agonists appear to show the same pre-clinical behavioural profile as what biased agonism is trying to achieve (Paton et al, 2020a.…”
Section: Alternative Paths To Non-addictive Analgesicsmentioning
confidence: 99%